2013
DOI: 10.11122/ijmeb.2013.9.20.293
|View full text |Cite
|
Sign up to set email alerts
|

Algılanan Destinasyon İmajının Tavsiye Davranışı Üzerine Etkisi: Safranbolu’da Bir Araştırma

Abstract: Araştırmanın temel amacı, algılanan destinasyon imajının, tavsiye etme durumu üzerine etkisini ortaya koymaktır. Bu amaca bağlı olarak, Safranbolu'yu ziyaret eden turistler üzerine bir araştırma gerçekleştirilmiştir. Yapılan bu çalışmada anket tekniği ile toplam 287 turistten veri elde edilmiştir. Elde edilen veriler SPSS 15 istatistik programı ile analiz edilmiştir. Araştırmada destinasyon imajı, hizmet ve üstyapı, huzurlu ortam, tarihi doku ve çevre ile altyapı boyutlarıyla ele alınmıştır. Bu bağlamda, algıl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
1
3
0
2
Order By: Relevance
“…These findings indicate that perceived destination image has a positive impact on visitors' satisfaction, revisit and recommendation intentions. Obtained results support the results of many studies found in the literature (Kozak and Rimmigton, 2000;Oppermann, 2000;Bigne et al, 2001;Cai et al, 2003;Lee et al, 2005;Chen and Tsai, 2007;Bigne et al, 2009;Lee, 2009a;Lee, 2009b;Wang and Hsu, 2010;Mohamad et al, 2011;İnan et al, 2011;Mohamad and Mokhlis, 2012;Lertputtarak, 2012;Sevim et al, 2013;Phillips et al, 2013;Lu et al, 2015;Yetiş and Kaygısız, 2015;Ramseook Munhurrun et al, 2015;Stylos et al, 2016;Prayogo and Kusumawardhani, 2016;Umur and Eren, 2016;Akbolat and Durmuş, 2017). However, it must be taken into account that each region has different dimensions and these dimensions have an impact on satisfaction, recommendation and revisit intentions.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings indicate that perceived destination image has a positive impact on visitors' satisfaction, revisit and recommendation intentions. Obtained results support the results of many studies found in the literature (Kozak and Rimmigton, 2000;Oppermann, 2000;Bigne et al, 2001;Cai et al, 2003;Lee et al, 2005;Chen and Tsai, 2007;Bigne et al, 2009;Lee, 2009a;Lee, 2009b;Wang and Hsu, 2010;Mohamad et al, 2011;İnan et al, 2011;Mohamad and Mokhlis, 2012;Lertputtarak, 2012;Sevim et al, 2013;Phillips et al, 2013;Lu et al, 2015;Yetiş and Kaygısız, 2015;Ramseook Munhurrun et al, 2015;Stylos et al, 2016;Prayogo and Kusumawardhani, 2016;Umur and Eren, 2016;Akbolat and Durmuş, 2017). However, it must be taken into account that each region has different dimensions and these dimensions have an impact on satisfaction, recommendation and revisit intentions.…”
Section: Discussionsupporting
confidence: 88%
“…In their study analyzing the impact of perceived destination image on recommendation behavior, Sevim et al (2013) found a positive relation between perceived destination image and tourists' behavior of recommendation. Yetiş and Kaygısız (2015) analyzed the impact of destination image on the future behavioral inclinations of tourists.…”
Section: Literature In the Fieldmentioning
confidence: 99%
“…When examining the literature, it is found that perceived country image has a high influence on tourists' behavior, purchase decision process and purchase intentions (Güzel, 2009;Sevim et al, 2013;Ateşoğlu & Türker, 2013;Aydın & Biçer, 2017). The fact that the knowledge, perceptions, and thoughts of the citizens of the region where the research was conducted about Turkey as a tourism destination have not been researched before shows the original value of this research.…”
Section: Introductionmentioning
confidence: 90%
“…It is important to distinguish between country image, which is the sum of beliefs about a country and influenced by economic, political, and geographic factors, and destination image, which refers to how the country is perceived as a destination (Alvarez & Korzay, 2008). The concept of destination image encompasses individual or collective mental thoughts or concepts about a destination and plays a key role in destination selection (Sevim, et al, 2013). Destination image has a greater impact on tourists' decision to choose a destination than the tangible products offered there and plays a more crucial role.…”
Section: Introductionmentioning
confidence: 99%
“…Bir destinasyonun turistler tarafından tercih edilmesinde sahip olduğu imajın olumlu olması oldukça önemli bir rol oynamaktadır. Çeşitli araştırmalar destinasyon imajının insanların satın alma karar sürecinde oldukça etkili bir olgu olduğunu göstermektedir (Sevim, Seçilmiş ve Görkem, 2013;Umur ve Eren 2015;Loi vd., 2017;Lourerio ve Jesus, 2019;Gün, Durmaz ve Tutcu, 2019;Mirzayeva, 2020;Yeşildağ, 2020;Çeti ve Atay, 2020).…”
Section: Introductionunclassified